Joint injury and rehabilitation of Chinese gymnasts - Li, G.; Yang, J.; Wang, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction: Chinese famous gym coaches Gao Jian and Qian Kui proposed that the gym field must put emphasis on scientific training and the prevention of injuries. The characteristics of Chinese gymnasts` joint injuries were studied so as to offer a reference for scientific training and medical supervision. Methods: A comprehensive review of the literature was conducted, field investigation, expert interview and statistical analyses were also undertaken. Results: In gymnasts` foot and ankle injuries, joint injury takes 72% and Tendon terminal injury takes 33%. In 120 ankle joints there are 261 parts of joint injury taking 218% of the total. All the gymnasts had bone injury. The knee periosteum injuries and acute knee joint injuries are universally common. The incidence of compound injuries for females 66.7%, and males 33.3%. Chronic injuries were 33.3% and the acute injuries were 66.7%. In female gymnasts` tuber ischiadicum bone epiphysis was 35.75% and happens during the ages of 12-14. Gymnasts` shinbone fracture was 52 8%, in children aged 8-16. Male gymnasts` elbow joint injuries were 70% and joint injuries take 85%. The symptom of their joint X ray shows abnormal bone epiphysis, ossein proliferation and bone fracture. Discussion / Conclusions: Juvenile gymnasts mainly have bone epiphysis injuries while the adult gymnasts have bone joint disease. The female gymnasts` tuber ischiadicum is the compound disease caused both by bone epiphysis necrosis due to the shortage of blood and rending fracture. Too early and long attendance of gym training is the important reason causing chronic injury and then vertebral facture. Individual adaption to gymnastics loads should be considered both in treatment and prevention of injury. Gymnasts`. Modern rehabilitation ideas should be indispensible for future sport injury rehabilitation.